Experimental analysis of sand-bearing muck blockages inside single circle earth pressure balance shield chambers. (March 2023) - Ji, Chang; Fu, Longlong; Zhou, Shunhua; Yao, Qiyu; He, Chao
Highlights: Muck flow parameters and shear plate torque near the chamber partition were measured by a self-developed model shield. Distinguishing index of muck occlusion occurrence based on muck flow angular velocity was proposed. Two types of sandy muck occlusion development processes were revealed. Muck occlusion identification method based on shear plate torque near the partition was proposed. The predictive capability of the proposed identification method was preliminarily validated by field data. Abstract: Sand-bearing muck occlusion in an earth pressure balance (EPB) shield chamber are difficult to distinguish in real-time, resulting in a delayed response and threatening the safety of construction processes. This study conducted a series of model tests to collect and analyse critical parameters, including the flow parameters and shear plate torque of sand-bearing muck near the chamber partition, the pressure in front of the cutter head and on the chamber partition. Two types of sandy muck occlusion development processes were revealed, which considered the muck flow angular velocity near the chamber partition dropped to zero as a unified characteristic index. A method for discriminating muck occlusion by the shear plate torque near the chamber partition was further proposed. Finally, the preliminary field verification of this discrimination method was carried out through the Hang-Bo shield interval of Zhengzhou Metro Line 3 in China. This study shows that when the sand-bearing muck near the chamber partition continually rotates around the central axis, the muck inside the chamber will not be blocked. However, once the muck located in the orientation mentioned above remains stationary, the stationary trend of the muck will continue to develop towards the cutter head, which will break the stable flow path of the muck inside the chamber. At the same time, the shear plate torque near the chamber partition will change from a periodic fluctuation form to a three-stage change form. These research results provide new insights and on-site guidance for the occurrence and identification of muck occlusion in single-circle EPB shield chambers in sand-bearing strata.